Pengaruh Pemberdayaan Usaha Kecil dan Menengah terhadap Pembangunan Ekonomi Masyarakat Kabupaten Karo - Serli Handayani Br. Surbakti; Ripho Delzy Perkasa (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
As a component of economic growth, small and medium enterprises (SMEs) are in a strategic position to accelerate structural change and improve people's livelihoods, especially in the Kabanjahe region of the Karo region. This study uses descriptive research with a qualitative approach. To accomplish this, the researchers went directly to the scene and interviewed one of his staff members working at his UKM in Kabanjahe district of Karorigency. In its role, SMEs can increase their own employment and become a source of sustainable business development and smooth income growth. This motivated researchers to explore approaches that would lead to success in the Kabanjahe area of ​​the Karo region. The purpose of this study was to investigate the extent to which the strengthening of SMEs affects the economic development of municipalities.